2006
DOI: 10.2298/hel0645043c
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Sclerotinia responses in Helianthus petiolaris

Abstract: Cultivated sunflower (Helianthus annuus L.) is susceptible to Sclerotinia sclerotiorum (Lib.) de Bary. H. petiolaris Nutt is a wild sunflower species naturalized in Argentina. The objective of this work was to evaluate the responses of some accessions of H. petiolaris to S. sclerotiorum inoculation in order to detect potential sources of resistance to be used in cultivated sunflower. An experiment was carried out at the UIB's experiment field. Inoculations were made on leaves and stems. Lesion mean on leaves w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Markers of introgressed zones of H. argophyllus, H. debilis, H. praecox, and H. petiolaris in the resistant lines are assumed to be good candidates to identify the segments carrying stalk rot-resistant quantitative trait loci (QTLs). The possibility of detecting H. petiolaris accessions with a high level of resistance to S. sclero tiorum than others is indicated (Caceres et al 2006). Independent QTLs, other than that for stalk rot resistance, have been identified for head rot resistance (Ronicke et al 2005a, Yue et al 2008).…”
Section: Molecular Breeding and Transgenic Sunflower For Resistance To Sclerotinia Diseases In Sunflowermentioning
confidence: 99%
“…Markers of introgressed zones of H. argophyllus, H. debilis, H. praecox, and H. petiolaris in the resistant lines are assumed to be good candidates to identify the segments carrying stalk rot-resistant quantitative trait loci (QTLs). The possibility of detecting H. petiolaris accessions with a high level of resistance to S. sclero tiorum than others is indicated (Caceres et al 2006). Independent QTLs, other than that for stalk rot resistance, have been identified for head rot resistance (Ronicke et al 2005a, Yue et al 2008).…”
Section: Molecular Breeding and Transgenic Sunflower For Resistance To Sclerotinia Diseases In Sunflowermentioning
confidence: 99%
“…Although different authors measured leaf lesions 4 to 7 days after inoculation (Degener et al 1998, Castano et al 1992a, Castano et al 1992b, Caceres et al 2006), in our case it was not possible due to slow progression of leaf lesions. One of the reasons for measuring leaf lesions later than 7 days after inoculation might be environmental conditions, especially high temperatures in the period immediately after artifi cial inoculation (Hahn 2002).…”
Section: Resultsmentioning
confidence: 60%
“…Cáceres et al (2006) found a high level of resistance to the same fungus in some Argentinean H. petiolaris accessions, and considered this species as a potential source for disease resistance in leaves and stems in sunflower breeding. Resistance to Phomopsis helianthi, a fungus which produces stem canker in sunflower was also found in H. petiolaris.…”
Section: Discussionmentioning
confidence: 92%
“…In fact, H. petiolaris was the donor of the male sterility source that made possible the production of sunflower commercial hybrids (Leclercq, 1969) and could have some other interesting traits (Covas and Vargas López, 1970;Ferreira, 1980). Cáceres et al (2006Cáceres et al ( , 2007 found genetic resistance to Sclerotinia sclerotiorum and Phomopsis helianthii in Argentinean germplasm.…”
mentioning
confidence: 99%